Jang : the soul of Korean cooking - Kang, Mingoo; Stein, Joshua David (Artisan, a division of Workman Publishing, 2024)
"Like butter in French cooking or olive oil in Italian, jangs are the soul of Korean cuisine. These umami sauces are found in every meal, from soups and stews, to salads, marinades, and even desserts, adding depth and complexity to every dish. The foundation of the three main jangs- gochujang, doenjang, and ganjang-is simple. Soybeans, water, and salt are dried, aged, and fermented in earthenware pots, extracting flavor from their environment and slowly blossoming into intensely flavored jangs. Few understand these ingredients better than chef Mingoo Kang, who has dedicated his Seoul restaurant to the exploration of jangs. In his first cookbook, Kang expertly weaves jangs' history and methods into 60 accessible recipes to bring the sauces to life. Dishes like Fish Dumplings and Gang-Doenjang Bibimbap showcase the sauces' traditional Korean roots, while Western-inspired recipes like Doenjang Crème Brulee and Ssamjang Cacio e Pepe reinvent favorite meals. Through artisan profiles, sidebars, and step-by-step photographs, Jang uncovers one the culinary world's best-hidden secrets"--